2002
DOI: 10.1177/104990910201900109
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pain and health-related quality of life in slowly progressive neuromuscular disease

Abstract: Few studies have examined the effect of pain on the quality of life of individuals with slowly progressive neuromuscular disease (NMD). The purpose of this study was to determine the frequency and extent to which subjects with slowly progressive NMD report pain and the association between pain and health-related quality of life in persons with NMD. The study design was a descriptive, nonexperimental survey. Of a total of 1,432 subjects with slowly progressive NMDs recruited from a university-based NMD clinic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
94
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 36 publications
14
94
1
3
Order By: Relevance
“…In total, five studies assessed the relationship between pain and QoL [6,9,21,30,31]. Of these, one study assessed associations between SF-36 ''bodily pain'' and the other SF-36 indices [31].…”
Section: Painmentioning
confidence: 99%
“…In total, five studies assessed the relationship between pain and QoL [6,9,21,30,31]. Of these, one study assessed associations between SF-36 ''bodily pain'' and the other SF-36 indices [31].…”
Section: Painmentioning
confidence: 99%
“…We were unable to cover the whole range of diseases that fall within this category, and thus focused on three common NMDs (ALS, FSHD, MG) that are representative of different aetiologies (neurodegenerative, neuroimmunological and hereditary) as well as time of onset [early (\20 years, FSHD), mid ([40 years, MG) or late ([55 years, ALS) life] and prognosis. Previous studies have evaluated either single NMDs [22,23,31,32,37] or concentrated on the influence of chronic pain or fatigue on the HRQoL in NMDs [1,20,21]. As mentioned in the introduction, comparisons between these studies are complicated by differences in the study designs and HRQoL-instruments used.…”
Section: Discussionmentioning
confidence: 96%
“…Disabilities such as multiple sclerosis (MS), neuromuscular disease (NMD), and spinal cord injury (SCI) are commonly associated with a number of chronic pain problems, including muscu-loskeletal pain (Abresch, Carter, Jensen, & Kilmer, 2002;Haisma et al, 2007;Kassirer, 2000), neuropathic pain or paresthesias (Ehde et al, 2003;Finnerup, Johannesen, Sindrup, Bach, & Jensen, 2001;Frisbie & Aguilera, 1990;Jensen, Abresch, Carter, & McDonald, 2005;Jensen, Hanley, Turner, & Cardenas, 2004;Siddal & Loeser, 2001), chronic headache (Archibald et al, 1994), and painful tonic spasms (Perkins, Moxley, & Papciak, 1999). Recent evidence has suggested that the majority of patients with these disabilities report chronic painful sensations (Ehde et al, 2003;Jensen et al, 2004;Widerstrom-Noga & Turk, 2003) and that from one fourth to one third report the pain as severe (Ehde et al, 2003;Jensen et al, 2004;Widerstrom-Noga & Turk, 2003).…”
Section: The Present Studymentioning
confidence: 99%